IMPROVING STUDENT’S SPEAKING SKILL THROUGH WORD RELAY GAME ON INTRODUCTION ONE-SELF MATERIAL IN MTSN 1 PROBOLINGGO - Tarwiyah, Lailatut; Hikmah, Durratul; Sulastri, Sulastri (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
Speaking skill is a crucial component of English language learning; however many EFL students experience anxiety, low confidence, and limited vocabulary when speaking. This classroom action reseacrh aimed to improve the speaking skill of seventh-grade students at MTsN 1 Probolinggo throught the implementetion of the Word Relay Game in self-introduction materials. The study applied two cycles following the Kemmis and McTaggart model, involving 25 students.data were collected through speaking tests, observation, and fiel notes. To overcome this, researchers combine the principles of Communicative Language Teaching (CLT) and Game-Based Learning (GBL) in an interesting and innovative teaching method. The results showed a significant increase in students' average scores from 36.92 in the pre-test, increasing to 60.60 in the first cycle, and reaching 89.40 in the second cycle. Overall learning completeness is achieved, where 100% of students can achieve the specified minimum grade. These resukts indicate that the Word Relay Game effectively enhances students pronounciation, fluency, vocabulary use, and speaking confidence. Therefore this strategy can be considered an effective and engaging alternative for teaching speaking skills in junior high scholl EFL classroom. development.